Application of Fe-Co / Al2O3 in preparation of high-calorific-value natural gas through hydrogenation of carbon dioxide
By using Fe-Co/Al2O3 catalyst, the problem of low CO2 conversion rate of Fe-based catalysts is solved, and efficient conversion of high-calorie natural gas is achieved through the use of Fe-Co/Al2O3 catalyst, and the CO2 utilization rate and natural gas calorific value are improved.
Patent Information
- Application Number
- CN202510171320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-17
AI Technical Summary
When CO2 is hydrogenated to prepare high-calorie natural gas, the CO2 conversion rate is low and it is difficult to achieve efficient utilization.
The Fe-Co/Al2O3 catalyst is used to control the element mass ratio of Fe, Co, Al, and use specific preparation methods and reduction conditions to improve the activity of the catalyst and CO2 conversion rate.
The CO2 conversion rate was significantly improved to 62.66%, and the calorific value of natural gas was increased to 47.83 MJ/Nm3, meeting the requirements of high-calorie natural gas and achieving efficient utilization of CO2.
Smart Images

Figure CN119838598A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide hydrogenation, and in particular to the application of a Fe-Co / Al2O3 catalyst in improving the carbon dioxide conversion rate in the preparation of high calorific value natural gas by carbon dioxide hydrogenation. Background Art
[0002] As a clean fuel, natural gas is mainly composed of CH4. It produces less air pollutants during combustion and is expected to replace other fuels or raw materials. Studies have found that CO2 can generate CH4 through hydrogenation, and based on this, there are various studies on methanation catalysts. However, due to the low calorific value of CH4 itself (37.74 MJ / Nm 3 ), the calorific value of natural gas with methane as the main component is low, and the consumption will be very large when used in fields such as power generation, so it is necessary to increase the calorific value of the produced natural gas.
[0003] There is no strict standard for the calorific value of high calorific value coal-to-gas, but it is generally considered to be more than 40 MJ / Nm 3 (10000kcal / Nm 3 ) is high calorific coal-to-gas natural gas, which requires that it must contain at least 5%-15% C2-C4 low-carbon alkanes. Existing research on the synthesis of high calorific value natural gas often uses CO as the carbon source, and the conversion rate can basically reach more than 90%, and the carburization of Fe is promoted by adding transition metal additives or changing pretreatment conditions, thereby promoting the formation of low-carbon alkanes. However, when CO2 is used as the carbon source, due to the chemical inertness of CO2 itself, the conversion rate is usually low, and it is difficult to achieve efficient utilization of CO2. The existing technology uses Fe-based catalysts to hydrogenate CO2 to prepare high calorific value natural gas. Although Fe-based catalysts have both RWGS and FTS reaction activities and can promote the growth of carbon chains, Fe-based catalysts generally have low activity and low CO2 conversion rate. The CO2 conversion rate is only more than 20%, and when catalyzing CO2 hydrogenation, it is also necessary to pay attention to its hydrogenation activity and the degree of carbon chain growth, otherwise it is easy to generate olefins or long-chain hydrocarbons. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an application of Fe-Co / Al2O3 catalyst to improve the carbon dioxide conversion rate in the preparation of high calorific value natural gas by carbon dioxide hydrogenation, thereby enhancing the catalytic activity of the Fe-based catalyst while ensuring the preparation of high calorific value natural gas, improving the CO2 conversion rate, and improving the CO2 utilization rate.
[0005] To achieve the above object, the present invention adopts the following technical solution: The present invention provides application of Fe-Co / Al2O3 catalyst in improving carbon dioxide conversion rate in preparing high calorific value natural gas by hydrogenation of carbon dioxide.
[0006] Furthermore, the element mass ratio of Fe, Co and Al in the Fe-Co / Al2O3 catalyst is 100:16:16.
[0007] Furthermore, the preparation method of the Fe-Co / Al2O3 catalyst comprises: Dissolve the precursor salts corresponding to the active component Fe, the carrier Al2O3 and the auxiliary agent Co in deionized water and mix and stir them thoroughly to obtain a precursor salt solution; Dissolving ammonia water in deionized water and stirring thoroughly to obtain an ammonia solution; The precursor salt solution is added dropwise into the ammonia solution under heating in a water bath, and the pH value is controlled so that the precursor solution is completely precipitated to obtain a mixed solution after titration; The mixed solution is aged, filtered and washed to obtain a filter cake; the obtained filter cake is dried and calcined to obtain a catalyst semi-finished product; the catalyst semi-finished product is tableted, pelletized and sieved to obtain Fe-Co / Al2O3 catalyst particles.
[0008] Furthermore, the precursor salts corresponding to the active component Fe, the carrier Al2O3 and the auxiliary agent Co are Fe(NO3)3•9H2O, Al (NO3)3•9H2O and Co(NO3)2•6H2O, respectively.
[0009] Further, the molar ratio of Fe(NO3)3•9H2O, Co(NO3)2•6H2O, Al (NO3)3•9H2O and ammonia water is 0.03:0.0046: 0.01: 0.129.
[0010] Furthermore, the precursor salt solution was added dropwise into the ammonia solution, the pH was controlled at 9-10, and the water bath temperature was controlled at 80 °C.
[0011] Further, the mixed solution was aged for 3.5 h; the aged mixed solution was filtered and washed, and the pH was controlled to be 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
[0012] Furthermore, the application includes: performing reduction treatment on the obtained Fe-Co / Al2O3 catalyst particles using a reducing atmosphere; and introducing a reaction raw material gas after the reduction is completed to perform a CO2 hydrogenation reaction.
[0013] Furthermore, the reducing atmosphere is hydrogen, and the reducing conditions are: normal pressure, pure hydrogen is introduced at 350° C. for reduction for 4 h, and the hydrogen flow rate is 30 mL / min.
[0014] Furthermore, the CO2 hydrogenation reaction conditions are: reaction temperature 320 °C, reaction pressure 3.0 MPa, H2 / CO2 molar ratio in the feed gas is 3.0, and feed gas flow rate is 10.75 mL / min.
[0015] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects: The Fe-Co / Al2O3 catalyst prepared by the present invention is used for the production of high calorific value natural gas by hydrogenation of CO2, and the calorific value of the generated natural gas can reach 47.83 MJ / Nm 3 , meeting the requirements of high calorific value natural gas. At the same time, the CO2 conversion rate can reach 62.66%, which greatly improves the CO2 conversion rate, improves the CO2 utilization rate, realizes the efficient utilization of CO2, and provides ideas for controlling carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD characterization diagrams of the Fe-Co / Al2O3 catalyst of Example 1 of the present invention and the catalysts of Comparative Examples 1-4; Figure 2 It is a comparison chart of the catalytic performance of the Fe-Co / Al2O3 catalyst of Example 1 of the present invention and the catalysts of Comparative Examples 1-4 at TOS=18 h. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.
[0018] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.
[0019] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources. Example
[0020] Weigh 12.12 g Fe(NO3)3•9H2O, 1.3258 g Co(NO3)2•6H2O, and 3.7333 g Al (NO3)3•9H2O respectively, dissolve them in 800 mL deionized water, and mix and stir them thoroughly for 30 min to obtain a precursor nitrate solution.
[0021] 19.8429 mL of 25% ammonia water was measured, diluted in 800 mL of deionized water and stirred for 30 min to obtain an ammonia solution.
[0022] The obtained precursor nitrate solution was dripped into the ammonia solution drop by drop, and the pH was controlled at about 9-10 to ensure that the precursor solution was completely precipitated. This process was carried out in a water bath heater, and the water bath temperature was maintained at 80 °C. After the precursor nitrate solution was added, the obtained mixed solution was aged for 3.5 h.
[0023] The aged mixed solution was filtered and washed, and the pH was controlled at about 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
[0024] After the calcined catalyst is cooled to room temperature, it is tableted, cut into pellets and sieved to obtain 20-40 mesh Fe-Co / Al2O3 catalyst particles (referred to as Fe-Co / Al).
[0025] 0.3 g of Fe-Co / Al2O3 catalyst particles were weighed and loaded into a reaction tube, and the reaction tube was placed in a fixed bed reactor for CO2 hydrogenation reaction. First, H2 reduction was carried out, and the reduction conditions were: normal pressure, pure H2 (30 mL / min) was introduced at 350 ℃ for 4 h; after the reduction was completed, the reaction gas was introduced for CO2 hydrogenation reaction, and the reaction conditions were: H2 / CO2=3.0, temperature of 320 ℃, reaction pressure of 3.0 MPa, and flow rate of 10.75 mL / min.
[0026] Comparative Example 1 Weigh 12.12 g of Fe(NO3)3•9H2O and 3.7333 g of Al (NO3)3•9H2O respectively and dissolve them in 800 mL of deionized water. Mix and stir them thoroughly for 30 min to obtain a precursor nitrate solution.
[0027] 18.441 mL of 25% ammonia water was measured, diluted in 800 mL of deionized water and stirred for 30 min to obtain an ammonia solution.
[0028] The obtained precursor nitrate solution was dripped into the ammonia solution drop by drop, and the pH was controlled at about 9-10 to ensure that the precursor solution was completely precipitated. This process was carried out in a water bath heater, and the water bath temperature was maintained at 80 °C. After the precursor nitrate solution was added, the obtained mixed solution was aged for 3.5 h.
[0029] The aged mixed solution was filtered and washed, and the pH was controlled at about 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
[0030] After the calcined catalyst is cooled to room temperature, it is tableted, cut into pellets and sieved to obtain 20-40 mesh Fe / Al2O3 catalyst particles (referred to as Fe / Al).
[0031] Weigh 0.3 g of Fe / Al2O3 catalyst particles and load them into the reaction tube, and place the reaction tube in a fixed bed reactor for CO2 hydrogenation reaction evaluation. First, H2 reduction was performed, and the reduction conditions were: normal pressure, pure H2 (30 mL / min) was introduced at 350 °C for 4 h. After the reduction was completed, the reaction gas was introduced for CO2 hydrogenation reaction, and the reaction conditions were: H2 / CO2=3.0, temperature was 320 °C, reaction pressure was 3.0 MPa, and flow rate was 10.75 mL / min.
[0032] Comparative Example 2 12.12 g Fe(NO3)3•9H2O, 1.3314 g Ni (NO3)2•6H2O, and 3.7333 g Al(NO3)3•9H2O were weighed separately and dissolved in 800 mL deionized water. The mixture was fully mixed and stirred for 30 min to obtain a precursor nitrate solution.
[0033] 19.8503 mL of 25% ammonia water was measured, diluted in 800 mL of deionized water and stirred for 30 min to obtain an ammonia solution.
[0034] The obtained precursor nitrate solution was dripped into the ammonia solution drop by drop, and the pH was controlled at about 9-10 to ensure that the precursor solution was completely precipitated. This process was carried out in a water bath heater, and the water bath temperature was maintained at 80 °C. After the precursor nitrate solution was added, the obtained mixed solution was aged for 3.5 h.
[0035] The aged mixed solution was filtered and washed, and the pH was controlled at about 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
[0036] After the calcined catalyst is cooled to room temperature, it is tableted, cut into pellets and sieved to obtain 20-40 mesh Fe-Ni / Al2O3 catalyst particles (referred to as Fe-Ni / Al for short).
[0037] Weigh 0.3 g of Fe-Ni / Al2O3 catalyst particles and load them into the reaction tube, and place the reaction tube in a fixed bed reactor for CO2 hydrogenation reaction evaluation. First, H2 reduction was performed, and the reduction conditions were: normal pressure, pure H2 (30 mL / min) was introduced at 350 °C for 4 h. After the reduction was completed, the reaction gas was introduced for CO2 hydrogenation reaction, and the reaction conditions were: H2 / CO2=3.0, temperature of 320 °C, reaction pressure of 3.0 MPa, and flow rate of 10.75 mL / min.
[0038] Comparative Example 3 12.12 g Fe(NO3)3•9H2O, 1.0164 g Cu (NO3)2•3H2O, and 3.7333 g Al(NO3)3•9H2O were weighed separately and dissolved in 800 mL deionized water. The mixture was fully mixed and stirred for 30 min to obtain a precursor nitrate solution.
[0039] 19.7333 mL of 25% ammonia water was measured, diluted in 800 mL of deionized water and stirred for 30 min to obtain an ammonia solution.
[0040] The obtained precursor nitrate solution was dripped into the ammonia solution drop by drop, and the pH was controlled at about 9-10 to ensure that the precursor solution was completely precipitated. This process was carried out in a water bath heater, and the water bath temperature was maintained at 80 °C. After the precursor nitrate solution was added, the obtained mixed solution was aged for 3.5 h.
[0041] The aged mixed solution was filtered and washed, and the pH was controlled at about 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
[0042] After the calcined catalyst is cooled to room temperature, it is tableted, cut into pellets and sieved to obtain 20-40 mesh Fe-Cu / Al2O3 catalyst particles (referred to as Fe-Cu / Al for short).
[0043] Weigh 0.3 g of Fe-Cu / Al2O3 catalyst particles and load them into the reaction tube, and place the reaction tube in a fixed bed reactor for CO2 hydrogenation reaction evaluation. First, H2 reduction was performed, and the reduction conditions were: normal pressure, pure H2 (30 mL / min) was introduced at 350 °C for 4 h. After the reduction was completed, the reaction gas was introduced for CO2 hydrogenation reaction, and the reaction conditions were: H2 / CO2=3.0, temperature of 320 °C, reaction pressure of 3.0 MPa, and flow rate of 10.75 mL / min.
[0044] Comparative Example 4 12.12 g Fe(NO3)3•9H2O, 1.2282 g Zn (NO3)2•6H2O, and 3.7333 g Al(NO3)3•9H2O were weighed separately and dissolved in 800 mL deionized water. The mixture was fully mixed and stirred for 30 min to obtain a precursor nitrate solution.
[0045] 19.7135 mL of 25% ammonia water was measured, diluted in 800 mL of deionized water and stirred for 30 min to obtain an ammonia solution.
[0046] The obtained precursor nitrate solution was dripped into the ammonia solution drop by drop, and the pH was controlled at about 9-10 to ensure that the precursor solution was completely precipitated. This process was carried out in a water bath heater, and the water bath temperature was maintained at 80 °C. After the precursor nitrate solution was added, the obtained mixed solution was aged for 3.5 h.
[0047] The aged mixed solution was filtered and washed, and the pH was controlled at about 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
[0048] After the calcined catalyst is cooled to room temperature, it is tableted, cut into pellets and sieved to obtain 20-40 mesh Fe-Zn / Al2O3 catalyst particles (referred to as Fe-Zn / Al for short).
[0049] Weigh 0.3 g of Fe-Zn / Al2O3 catalyst particles and load them into the reaction tube, and place the reaction tube in a fixed bed reactor for CO2 hydrogenation reaction evaluation. First, H2 reduction was performed, and the reduction conditions were: normal pressure, pure H2 (30 mL / min) was introduced at 350 °C for 4 h. After the reduction was completed, the reaction gas was introduced for CO2 hydrogenation reaction, and the reaction conditions were: H2 / CO2=3.0, temperature of 320 °C, reaction pressure of 3.0 MPa, and flow rate of 10.75 mL / min.
[0050] Figure 1 The XRD characterization diagrams of the catalysts of Example 1 and Comparative Examples 1-4 of the present invention are shown in FIG. Figure 1 It can be seen that the catalysts of Example 1 and Comparative Examples 1-4 all have peaks belonging to Fe3O4 at 30.36°, 35.77°, 37.41°, 43.47°, 57.51°, and 63.17°, which are the active phases of the RWGS reaction, indicating that the Fe species has been reduced. In particular, the FeCo alloy phase also appears on the Fe-Co / Al2O3 catalyst, which is generally considered to be the active phase of the FTS reaction. The appearance of this phase indicates that Fe-Co / Al2O3 has a certain ability to generate short-chain hydrocarbons.
[0051] Figure 2 The catalytic performance comparison diagram of the catalysts of Example 1 of the present invention and Comparative Examples 1-4 at TOS=18 h. Figure 2 It can be seen that the CO2 conversion rate of Fe / Al2O3 is low, only 26.83%. After Ni doping, the CO2 conversion rate and CH4 selectivity (95.63%) can be significantly improved, but the C2-C4 selectivity is reduced. The addition of Co mainly reduces the activity of RWGS, CO2 is mainly converted to CH4, C2-C4 0The selectivity is 24.57%, and the CO2 conversion rate is significantly improved compared to Fe / Al2O3, reaching 62.66%. Cu has RWGS activity. Adding Cu to Fe / Al2O3 can promote CO2 conversion (CO2 conversion rate 35.76%), but CO selectivity is higher. Cu promotes C2-C4 = The secondary transformation showed a higher C 5+ Selectivity. Compared with Fe / Al2O3, the addition of Zn promoter has a significant effect on C2-C4 and C 5+ The selectivity for CH4 was slightly improved, and the selectivity for CH4 was relatively low, but the CO2 conversion rate was only slightly improved to 29.29%.
[0052] The reason why adding transition metal additives causes changes in catalytic performance is that after adding Ni additives, since Ni itself has strong hydrogenation ability, the hydrogen activation ability of the catalyst surface will be significantly enhanced, which will have a greater impact on the product distribution, causing the reaction to favor methanation. After adding Co additives, the hydrogenation activity of the catalyst can also be improved, but the effect is not as significant as Ni, and the appearance of FeCo alloys can promote the formation of short-chain hydrocarbons, so it can promote CO2 conversion while having a certain selectivity for low-carbon hydrocarbons. After adding Cu additives, since Cu itself has RWGS reaction activity, the CO selectivity is significantly improved, and the addition of Cu can promote the adsorption of olefins, resulting in secondary conversion of olefins, so C 5+ The selectivity is significantly increased. After adding Zn, the adsorption capacity of H2 is weakened, thereby inhibiting the hydrogenation of olefins, so its olefin-alkane ratio is the highest.
[0053] The calorific value of the product gas of catalytic CO2 hydrogenation of the catalysts prepared in the examples of the present invention and the comparative examples at TOS=18 is shown in Table 1: Table 1 Heating value of CO2 hydrogenation product gas catalyzed by various catalysts at TOS=18 catalyst <![CDATA[Higher calorific value (MJ / Nm 3 )]]> <![CDATA[Lower calorific value (MJ / Nm 3 )]]> <![CDATA[Fe / Al2O3]]> 63.79 63.32 <![CDATA[Fe-Ni / Al2O3]]> 37.31 35.99 <![CDATA[Fe-Co / Al2O3]]> 47.68 46.50 <![CDATA[Fe-Cu / Al2O3]]> 71.43 71.41 <![CDATA[Fe-Zn / Al2O3]]> 65.48 65.12 As shown in Table 1, compared with Fe / Al2O3 catalyst, the calorific value of natural gas produced by adding Cu and Zn is improved, which is because their addition promotes the formation of hydrocarbons with higher carbon numbers. Since Ni is mainly used to promote methanation, the selectivity of CH4 reaches 95.63%. The calorific value of natural gas drops sharply after adding Ni additive. The addition of Co improves the selectivity of CH4, although C2-C4 0 The selectivity is reduced, but it can still be maintained at 24.57%, and the calorific value of the produced natural gas can reach 47.68 MJ / Nm 3 , meeting the requirements of high calorific value natural gas.
[0054] Although the calorific value of the produced natural gas has increased after adding Cu and Zn, the CO2 conversion rate is still low, only 35.76% and 29.29%. Although the addition of Ni additives can greatly improve the CO2 conversion rate, the calorific value of natural gas drops sharply and cannot meet the requirements of high calorific value natural gas. After adding Co, the CO2 conversion rate has been greatly improved to 62.66%, which significantly improves the CO2 utilization rate, and the calorific value of the product gas still meets the requirements of high calorific value natural gas. Therefore, Co is the most ideal additive.
[0055] The present invention has been disclosed above with preferred embodiments, but they are not intended to limit the present invention. Any technical solutions obtained by adopting equivalent replacement or equivalent transformation solutions fall within the protection scope of the present invention.
Claims
1. Application of Fe-Co / Al2O3 catalyst in improving the carbon dioxide conversion rate in the production of high calorific value natural gas by carbon dioxide hydrogenation.
2. The use according to claim 1, characterized in that: The element mass ratio of Fe, Co and Al in the Fe-Co / Al2O3 catalyst is 100:16:
16.
3. The use according to claim 1, characterized in that: The preparation method of the Fe-Co / Al2O3 catalyst comprises: Dissolve the precursor salts corresponding to the active component Fe, the carrier Al2O3 and the auxiliary agent Co in deionized water and mix and stir them thoroughly to obtain a precursor salt solution; Dissolving ammonia water in deionized water and stirring thoroughly to obtain an ammonia solution; The precursor salt solution is added dropwise into the ammonia solution under heating in a water bath, and the pH value is controlled so that the precursor solution is completely precipitated to obtain a mixed solution after titration; The mixed solution is aged, filtered and washed to obtain a filter cake; the obtained filter cake is dried and calcined to obtain a catalyst semi-finished product; the catalyst semi-finished product is tableted, pelletized and sieved to obtain Fe-Co / Al2O3 catalyst particles.
4. The use according to claim 3, characterized in that: The precursor salts corresponding to the active component Fe, the carrier Al2O3 and the auxiliary agent Co are Fe(NO3)3•9H2O, Al (NO3)3•9H2O and Co(NO3)2•6H2O respectively.
5. The use according to claim 4, characterized in that: The molar ratio of Fe(NO3)3•9H2O, Co(NO3)2•6H2O, Al (NO3)3•9H2O and ammonia water is 0.03: 0.0046: 0.01: 0.
129.
6. The use according to claim 3, characterized in that: The precursor salt solution was added dropwise into the ammonia solution, the pH was controlled at 9-10, and the water bath temperature was 80 °C.
7. The use according to claim 3, characterized in that: The mixed solution was aged for 3.5 h; the aged mixed solution was filtered and washed, and the pH was controlled to be 7; the obtained filter cake was dried at 80 °C for 12 h and calcined at 450 °C for 5 h.
8. The use according to claim 3, characterized in that: The obtained Fe-Co / Al2O3 catalyst particles are subjected to reduction treatment in a reducing atmosphere; after the reduction is completed, a reaction raw material gas is introduced to carry out a CO2 hydrogenation reaction.
9. The use according to claim 8, characterized in that: The reducing atmosphere is hydrogen, and the reducing conditions are: normal pressure, pure hydrogen is introduced at 350°C for 4 h, and the hydrogen flow rate is 30 mL / min.
10. The use according to claim 8, characterized in that: The CO2 hydrogenation reaction conditions are as follows: reaction temperature 320 °C, reaction pressure 3.0 MPa, H2 / CO2 molar ratio in the feed gas of 3.0, and feed gas flow rate of 10.75 mL / min.
Citation Information
Patent Citations
Iron-based catalyst for low-carbon olefin production through CO2 hydrogenation, and preparation and applications thereof
CN106031871A
Iron-based catalyst for preparing low-carbon olefin through CO2 hydrogenation and application thereof
CN107497437A
Catalyst for co-production of low carbon alkenes from carbon dioxide hydrogenation to gasoline and preparation method of catalyst
CN110586108A
Method for synthesizing low-carbon olefin through carbon dioxide hydrogenation by adopting iron-based catalyst
CN112169799A
Tandem catalyst for preparing aromatic hydrocarbon through direct hydrogenation of carbon dioxide as well as preparation method and application of tandem catalyst
CN115155588A